Distinct pathological profiles of inmates showcasing cluster B personality traits, mental disorders and substance use regarding violent behaviors. (February 2018) - Dellazizzo, Laura; Dugré, Jules R.; Berwald, Marieke; Stafford, Marie-Christine; Côté, Gilles; Potvin, Stéphane; Dumais, Alexandre
Abstract: High rates of violence are found amid offenders with severe mental illnesses (SMI), substance use disorders (SUDs) and Cluster B personality disorders. Elevated rates of comorbidity lead to inconsistencies when it comes to this relationship. Furthermore, overlapping Cluster B personality traits have been associated with violence. Using multiple correspondence analysis and cluster analysis, this study was designed to differentiate profiles of 728 male inmates from penitentiary and psychiatric settings marked by personality traits, SMI and SUDs following different violent patterns. Six significantly differing clusters emerged. Cluster 1, " Sensation seekers ", presented recklessness with SUDs and low prevalence's of SMI and auto-aggression. Two clusters committed more sexual offenses. While Cluster 2, " Opportunistic-sexual offenders ", had more antisocial lifestyles and SUDs, Cluster 6, "Emotional-sexual offenders", displayed more emotional disturbances with SMI and violence. Clusters 3 and 4, representing " Life-course-persistent offenders ", shared early signs of persistent antisocial conduct and severe violence. Cluster 3, " Early-onset violent delinquents ", emerged as more severely antisocial with SUDs. Cluster 4, " Early-onset unstable-mentally ill delinquents", were more emotionally driven, with SMI and auto-aggression. Cluster 5, " Late-start offenders", was less severely violent, and emotionally driven with antisocial behavior beginning later. This study suggests the presence of specific psychopathological organizations in violent inmates. Highlights: Cluster analysis elicited profiles of inmates from prison and psychiatric settings. High-risk inmates with specific psychopathological organizations are identified. 6 significantly differing clusters emerged. Crucial to integrate personality & behavioral based methods to comprehend violence.